Inpatient and outpatient health care utilization and expenditures among older adults aged 50 years and above in India - Anand, Ankit (Health Prospect, 2016)
Background: Social and economic inequality in utilization of health care services, as well as high out of pocket expenditures are prevalent in overall Indian population. The situation among older adults will be much more critical as they require long-term health care services. The objective of this study is to assess the utilization of outpatient and inpatient care among older adults and incurred out of pocket health expenditure. It also tried to explore the association between socioeconomic factors on receiving health care services and out of pocket health expenditure among older adults in India. Data source: The data from the Study on Global Ageing and Adult Health (SAGE) Wave 1 was used, which was conducted in 2007-08 in India. Respondents aged 50 and above are taken as older adult population. The final sample size was 7150 respondents aged 50 years and above. Results: The percentage of older adults aged 50 years and above receiving outpatient and inpatient health care service were 87.5% and 14.6% respectively. The use of private health facilities was high compared to government health facility. High utilization of outpatient among women and high use of inpatient care among men were found, which was insignificant after adjusting for other variables. Socioeconomic characteristics also play an important role in access to health care among older adults. Place of residence, marital status, caste, education and presence of morbidity were related to the utilization of health care services. Place of residence, education and wealth quintile were also significantly associated with health expenditures. Conclusion: Requirement of long-term health care among older adult population may result in increasing burden of health care expenditures. Socioeconomic characteristics also play an important role in access to health care among older adults. Developing quality and affordable health care services for older adults to ensure equity in accessibility and affordablility will be a major task for the public health system in India.